Food security and trade negotiations in the World Trade Organization: a cluster analysis of country groups - Díaz-Bonilla, Eugenio; Thomas, Marcelle; Robinson, Sherman; Cattaneo, Andrea (International Food Policy Research Institute, 2000)
An important issue in WTO trade negotiations is whether further liberalization of trade and agricultural policies may help or hinder food security in WTO member countries, especially the developing countries. The WTO recognizes various classifications of countries: developed, developing, least developed (LDC) and net food importing developing (NFIDC). How well do these categories capture issues of food security? This paper employs various methods of cluster analysis (including an approach based on fuzzy sets) and data for 167 countries to identify groups of countries categorized according to five measures of food security: food production per capita, the ratio of total exports to food imports, calories per capita, protein per capita, and the share of the non-agricultural population share. The analysis identifies 12 distinct clusters characterized by similarities and differences across the various measures. The analysis suggests that the LDC category consists of largely food insecure countries, but that there also are food insecure countries that are not LDCs. NFIDCs is less precise as an indicator of food vulnerability, with more than a third of those countries not falling under any of the food insecure groups. Also, the general category of “developing countries” is very heterogeneous and is not very useful if the focus is on issues of food security. Finally, our typology shows that all developed countries are included in food secure categories.